Identification of bat trypanosomes from Minas Gerais state, Brazil, based on 18S rDNA and Cathepsin-L-like targets (2018)
Several bat species can be infected by trypanosomes, but there is not much information about which of these parasites infect bats from Triângulo Mineiro and Alto Paranaíba, Minas Gerais state, Brazil, a formerly endemic region for Trypanosoma cruzi, the causative agent of Chagas disease. The aim of this study was to describe, characterize, and identify the presence of trypanosomes in bats. The captured bats (448) belong to four families and to 19 different species. Of those, 37 bats were found to be positive for trypanosomes by microhematocrit, (infection rate 8.3%) and 27 were positive after hemoculture analysis. Initially, the isolates were identified by PCR (18S rDNA, 24S? rDNA, spliced leader, COII RFLP-PCR) using primers originally designed for T. cruzi. PCRs (18S rDNA, 24S? rDNA) showed compatible bands for TcI, whereas COII RFLP-PCR showed a similar pattern associated to TcII. However, there was no DNA amplification using spliced leader as a target, revealing a discrepancy between the results. Phylogenetic analysis of Cathepsin L-like and 18S rDNA sequences proved that 15 of the isolates corresponded to Trypanosoma cruzi marinkellei and one to Trypanosoma dionisii. These results revealed that the diversity of trypanosome species in a region considered endemic for Chagas disease is greater than previous descriptions. All this can confirm the necessity of using DNA sequencing approaches in order to determinate trypanosomes species isolated from bats. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.